Performance management from the bottom up. Issue 1 (2nd January 2022) - Gassner, Drorit; Gofen, Anat; Raaphorst, Nadine
ABSTRACT: Current interest in middle-managers' compliance with performance management (PM) reforms focuses on their downward roles. To explore their understudied upward roles, this analysis draws on police chiefs' voice directed to senior management regarding the Israeli PM system as documented since its first introduction in 1999, and as reported both by chiefs and senior managers (N = 54). Unfolding four patterns of inconsistencies between PM systems' design and the operational, daily, course-of-work, close-to-the-field managers' upward roles allows us to move beyond criticism to constructive efforts, and provides new insights for reconciling the well-documented gap between policy intentions and outcomes in PM reforms.